Pendidikan dalam Perspektif Hadis - Hasbi Siddik (LPPM IAIN Sorong, 2018)
This paper will explore education in the perspective of Hadith, both the meaning, the nature, and the practice of education, as well as its urgency. In the books of Hadis (al-kutub al-tis’ah) there are many themes that talk about education. In the books it is mentioned a lot of terms tarbiyah, ta'lim, ta'dib, and other terms associated with it such as ‘ilm, al-aql, al-fikr, al-hikmah, and so on. The number of Hadis proves that the Prophet during his life did pay special attention to the issue of education. The search for an educational theme in the Hadis is a thematic study method (syarh al-mawdhui). The results of this study found that there are at least five themes in the Hadis on education: 1) the primacy of education (educating children); 2) the urgency of teaching science (in education); 3) the reward obtained for the learners; 4) fitrah (for children) to learn in education; 5) education from an early age (the obligation of parents to educate their children in worship or praying)